Strategi Digital Leadership untuk Mendorong Innovation Work Behaviour di Lembaga Keuangan Koperasi Simpan Pinjam - Reni, Reni; Renaldi; Amri; Akhmad Dahlan; Ahmad Muktamar (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to identify digital leadership strategies that are effective in improving employees' work innovation behavior at Sinar Murni Banten Savings and Loan Cooperative. Using a quantitative approach with survey techniques, data was collected from 100 cooperative employees who have at least one year of work experience and are involved in the use of digital technology in their daily work. The results showed that digital leadership has a significant influence on employees' creativity, proactivity, and ability to implement new ideas. Regression analysis revealed that digital leadership strategies contributed 37% to the variability of employees' innovative work behavior. Leaders who integrate digital technology in their managerial strategies can encourage employees to be more creative and proactive in completing their tasks. In conclusion, an effective digital leadership strategy can improve operational efficiency and create added value for cooperatives through the development of employee work innovation behavior. This research suggests that cooperatives should continue to develop technological infrastructure, initiatives to face challenges and capitalize on opportunities in the digital era